Characterization and Morphological Distribution of Ethylene Content in Impact Propylene Copolymers. Issue 1 (15th February 2018) - Santonja‐Blasco, Laura; Rungswang, Wonchalerm; Alamo, Rufina G.
Abstract : The effect of ethylene content, in a range between 8 and 11 mol%, and distribution on the solid‐state morphology of five impact polypropylene copolymers (IPC) have been studied via SEM, fractionation and microstructural characterization via gel permeation chromatography (GPC), high‐temperature thermal‐gradient interaction chromatography (HT‐TGIC), and differential scanning calorimetry (DSC). All copolymers display heterophasic morphology, with rubbery droplets randomly distributed in a predominant i PP matrix. While the mass fraction of amorphous ethylene‐propylene rubber molecules is very similar for all IPC studied, the size of the droplets increases from 0.6 to 1.1 μm with increasing ethylene content. This change in droplet size is correlated with changes in the composition of the crystalline ethylene‐propylene (CEP) component extracted via fractionation.